Use of the Information Security Index (KAMI) 4.2 as an Evaluation Method at the Paser Regency Communication, Informatics, Statistics and Coding Service - Nikita Samantha; Dwi Arief Prambudi; I Putu Deny Arthawan Sugih Prabowo (Jurnal Teknologi dan Manajemen, 2024)
Paser Department of Communication, Informatics, Statistics, and Cryptography (Diskominfostaper) is a regional institution tasked to providing information on regional development and public service provider. Based on Kominfo regulation No. 4 of 2016, Diskominfostaper Paser district as a local government apparatus, requires implementation and supervision related to information security in order to safeguard all managed information. However, the current information security is still weak because there has never been an evaluation of information security either independently (self-assessment) or from an external party, as a results there are still attempts to hack the system and involvement of third parties without any formal contracts. In this research, an evaluation of information security was carried out at the Diskominfostaper Paser Regency using the Index KAMI 4.2 with the ISO/IEC 27001: 2013 standard to determine the level of information security readiness. The results of the evaluation were obtained with an overall final score of 220 and a final score in the Electronic System (SE) category of 30 which was included in "High" category, thus indicating that information security is currently in the "Inadequate" Preparedness Level status with a Maturity Level of level I to level II. As a result, 95dihasilkan rekomendasi perbaikan pada enam area penilaian Indeks KAMI 4.2 guna meningkatkan pemenuhan status Tingkat Kelengkapan dalam memenuhi Kerangka Dasar ISO/IEC 27001:2013.